1991
DOI: 10.1016/0741-5214(91)90076-7
|View full text |Cite
|
Sign up to set email alerts
|

Is routine CT scanning necessary in the preoperative evaluation of patients undergoing carotid endarterectomy?

Abstract: To evaluate the usefulness of CT scanning before carotid endarterectomy, a prospective study was performed on 469 consecutive patients considered for carotid endarterectomy during a 5-year period. All patients underwent carotid duplex scanning and CT scanning before carotid arteriography. Two hundred thirty-seven patients (51%) had transient ischemic attacks, 109 (23%) had a prior stroke, and 122 (26%) were asymptomatic. Results of the CT scan were abnormal in 68 (62%) of the 109 patients with stroke. Fifty-on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Particular features of our study were that: (1) in patients selected for early CEA using our selection criteria, CT/MRI detected cerebral infarcts did not influence the risk of adverse events after surgery; (2) contralateral ICA occlusion was predictive of the need for intraluminal shunting; (3) shunting was used selectively in patients operated under general anesthesia; and (4) all surgical procedures were eversion CEA. As in other reports 11,25 and our own earlier study, 15 any cerebral infarcts on preoperative cerebral images, whatever their location and size, did not affect the risk of subsequently developing neurological impairments after early CEA. Paty et al 18 found, however, that the risk for permanent neurological deficits after CEA increased by a factor of 1.7 per each centimeter in the diameter of the preoperative infarct, suggesting that patients with larger infarcts are at greater risk of postoperative neurological adverse events.…”
Section: Discussionsupporting
confidence: 61%
“…Particular features of our study were that: (1) in patients selected for early CEA using our selection criteria, CT/MRI detected cerebral infarcts did not influence the risk of adverse events after surgery; (2) contralateral ICA occlusion was predictive of the need for intraluminal shunting; (3) shunting was used selectively in patients operated under general anesthesia; and (4) all surgical procedures were eversion CEA. As in other reports 11,25 and our own earlier study, 15 any cerebral infarcts on preoperative cerebral images, whatever their location and size, did not affect the risk of subsequently developing neurological impairments after early CEA. Paty et al 18 found, however, that the risk for permanent neurological deficits after CEA increased by a factor of 1.7 per each centimeter in the diameter of the preoperative infarct, suggesting that patients with larger infarcts are at greater risk of postoperative neurological adverse events.…”
Section: Discussionsupporting
confidence: 61%
“…38,39 Because this study involved only a selected number of AMCs, the results have limited generalizability to other hospitals, although previous research would indicate similar trends are occurring in community hospitals. 1,[11][12][13]40 Finally, more research is needed to develop validated risk-adjusted algorithms for CEA as has been developed for coronary artery bypass grafting. 41 Preliminary work suggests that risk-adjusted models can be developed from databases for patients undergoing a CEA.…”
mentioning
confidence: 99%
“…As shown in Table 2, of the 68 symptomatic patients who underwent CEA, 16.32 would have been anticipated to have had an ipsilateral stroke within 1'/a years if they were not operated on. The estimated costs for the medical care of the strokes avoided in the symptomatic patients were $2,405,201 as shown in Table 4.…”
Section: In 68 Symptomatic Patientsmentioning
confidence: 99%
“…Computed tomography (CT) scans of the brain were employed in only three patients, all with small or evolving strokes to document the presence of intracerebral bleeding and were not obtained routinely because of the low risk of other brain conditions being present in our experience and as determined by Martin et a1. 16 Magnetic resonance imaging (MRI) was used in some patients with marginal carotid lesions to determine if there were subclinical cerebral infarcts.l~ MRI studies with gadolinium and/or technetium nuclear brain scans were used in patients with recent strokes or rapidly improving neurologic deficits to determine if there was enhancement on the MRI study or an area of radioisotope accumulation on the nuclear brain scan indicative of compromise of the bloodbrain barrier. If the blood-brain barrier was compromised, CEA was postponed because of the risk of a potentially devastating intracerebral hemorrhage.'…”
Section: Diagnostic Costsmentioning
confidence: 99%